Pelogeniinae Chamberlin, 1919 (Annelida, Sigalionidae) from the Grand Caribbean Region - Cruz-Gómez, Christopher (European Journal of Taxonomy, 2022)
The marine annelid family Sigalionidae is little known in the Grand Caribbean Region; there are few records of these worms in the area, and some of the recorded species have uncertain taxonomic status. In this contribution, the subfamily Pelogeniinae was addressed through a faunistic study, aiming to improve the knowledge of Sigalionidae in the region. In order to do this, material deposited in the three following institutions was examined: University of Miami Deep Sea Expeditions; Florida Museum of Natural History, University of Florida, Gainesville; and El Colegio de la Frontera Sur, Chetumal. Eleven species are recognized, including six newly described: Dayipsammolyce paulayi sp. nov., Hartmanipsammolyce pettiboneae sp. nov., Neopsammolyce fragilis sp. nov., Pelogenia brevipalpata sp. nov., P. capitata sp. nov. and P. salazarvallejoi sp. nov. Four other species are confirmed for this region: N. floccifera (Augener, 1906), P. hartmanae Pettibone, 1997, P. kinbergi (Hansen, 1882) and Psammolyce flava Kinberg, 1856; and one is indeterminate: N. aff. floccifera. A standardized terminology of neurochaetae is proposed, along with notes on the notochaetal morphology and elytral structures. For all genera covered in this study, identification keys are also provided.